Genotypic Frequency in Asian Native Chicken Populations and Gene Expression Using Insulin-like Growth Factor 1 (IGF1) Gene Promoter Polymorphism - Hla Hla Moe; Takeshi Shimogiri; Kotaro Kawabe; Masahide Nishibori; Shin Okamoto; Tsutomu Hashiguchi; Yoshizane Maeda (The Journal of Poultry Science, 2009)
A single nucleotide polymorphism (SNP) site, alleles A and C, within promoter region of insulin-like growth factor 1 gene (IGF1) showed significant association with chicken growth, body composition and skeletal traits. In the present study, we performed genotyping of this SNP in Asian native chicken populations, layer and broiler populations using PCR-RFLP and comparison of gene expression level and growth traits among the SNP genotypes. By the PCR-RFLP, allele C frequency was estimated to be within the range of 0.64-1.00 in 12 Asian native chicken populations, 0.48-1.00 in eight layer stocks and 0.00-0.14 in two broiler stocks examined in this study. In all chicken populations, the observed number of each SNP genotype was in good agreement with the Hardy-Weinberg expectations. Body weight (BW), average daily gain (ADG), growth rate and IGF1 gene expression level in three-week liver were compared among three SNP genotypes obtained by AC×AC crossing. The rankings of each genotype with respect to BW, ADG and growth rate were AA>AC>CC, and statistical significance (P<0.05) was found within AA and CC in BW and ADG. The rankings of each genotype with respect to the IGF1 gene expression level was AC>AA>CC. Although we could not find statistically significant difference among the genotypes in the growth rate and the gene expression level, the mean values of CC were lower than those of AA in all traits.